2018
DOI: 10.1292/jvms.17-0477
|View full text |Cite
|
Sign up to set email alerts
|

Encephalitis induced by a newly discovered ruminant rhadinovirus in a free-living Formosan sambar deer (<i>Rusa unicolor swinhoei</i>)

Abstract: We documented a case of a free-living Formosan sambar deer (Rusa unicolor swinhoei) infected with a newly discovered ruminant Rhadinovirus (RuRv). Non-purulent encephalitis was the primary histological lesion of the sambar deer. We conducted nested PCR to screen for herpesvirus using generic primers targeting the DNA polymerase gene. In addition, we found that DNA polymerase gene of the sambar deer RuRv was present in the macrophage distributed in the Virchow Robin space with histopathologic lesions by chromog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Rhadinovirus infections have been reported a few times in cervids; encephalitis has been observed in a free-ranging Sambar deer as the only associated pathology (Chang et al. 2018 ), while other studies have detected Rhadinovirus in cervids but without any pathological damage confirmed (McKillen et al. 2017 ; Patel et al.…”
Section: Discussionmentioning
confidence: 99%
“…Rhadinovirus infections have been reported a few times in cervids; encephalitis has been observed in a free-ranging Sambar deer as the only associated pathology (Chang et al. 2018 ), while other studies have detected Rhadinovirus in cervids but without any pathological damage confirmed (McKillen et al. 2017 ; Patel et al.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, the genus Rhadinovirus included all herpesviruses that cause MCF in cervids and other ungulates; in 2005, this clade was moved to the Macavirus genus by the International Committee on Taxonomy of Viruses. Currently, only one report of encephalitis induced by a newly discovered ruminant Rhadinovirus (RuRv) has been reported, in a free-ranging Formosan sambar deer ( Rusa unicolor swinhoei ) ( 54 ). It is notable that seven uteruses from hinds that were aborted were positive for cervid Rhadinovirus type-2 (CRhV-2) through PCR in a deer farm in New Zealand; however, the role of the virus in abortion needs clarification ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sambar ( Rusa unicolor )is the most widely spread deer in Asian continent (Chang et al, 2018; Chellappandian et al, 2014; Forsyth et al, 2014; Li, Ba, & Yang, 2016; Lin, Pei, Wang, & Liu, 2014; Oria et al, 2015; Radhakrishnan et al, 2012; Somma, Moura, Lange, Medeiros, & Montiani-Ferreira, 2016),that range from Sri Lanka(Rajapaksha, Thilakaratne, Chandrasiri, & Niroshan, 2002), India(Ajith Kumar et al, 2018; Pothana, Devi, & Goel, 2017), Southern Nepal(Thapa & Kelly, 2017), Burma(Gupta et al, 2018),throughout Southern China (Lin et al, 2014) and in South-Eastern Asia to the Pacific Coast and the islands of Borneo and Hainan (Ajith Kumar et al, 2018; Bhattacharjee & Franzmann, 1986; Brodie et al, 2015; Brodie, Helmy, Brockelman, & Maron, 2009; Hoogstraal & Wassef, 1982; Ismail & Jiwan, 2015; Jerrett, Slee, & Robertson, 1990). For the family Cervidae, most of the knowledge on reproductive biology has been originated from studies of temperate species that exhibit a distinct seasonal cycle of reproductive behavior and antler growth in males (Bhattacharjee & Franzmann, 1986; Chan, Tsai, Chen, Tung, & Chang, 2009; Lin et al, 2014; Muir et al, 1997; Vongpralub et al, 2015).…”
Section: Introductionmentioning
confidence: 99%